2003
DOI: 10.1007/s00381-003-0753-x
|View full text |Cite
|
Sign up to set email alerts
|

Ependymoma

Abstract: This review article examines the current status of histopathological and cytogenetic diagnosis, surgical, chemotherapeutic and radiotherapeutic treatment and future directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 99 publications
1
23
0
Order By: Relevance
“…Intracranial tumors are predominant in pediatric patients (90%), whereas most adults show spinal manifestation (60%; refs. 3,4). Spinal tumor localization is usually associated with a favorable prognosis after gross total resection and does not need to be treated with adjuvant therapy (5,6).…”
mentioning
confidence: 99%
“…Intracranial tumors are predominant in pediatric patients (90%), whereas most adults show spinal manifestation (60%; refs. 3,4). Spinal tumor localization is usually associated with a favorable prognosis after gross total resection and does not need to be treated with adjuvant therapy (5,6).…”
mentioning
confidence: 99%
“…The LOH studies have identified LOH of 22q as the most frequent change in approximately 30% of ependymomas, 267 contributed partially by the loss or structural abnor- 267 A SKY analysis has been performed in one case of ependymoma reported by our group, 257 and showed no additional structural aberrations from the original Gbanded karyotype (http://www.ncbi.nlm.nih.gov/sky/) (Fig. 2).…”
Section: Neurosurg Focus / Volume 19 / November 2005mentioning
confidence: 95%
“…Ependymomas are well-delineated, moderately cellular gliomas and are the third most common brain tumors in children. 267 The WHO classification differentiates four major types: ependymoma (WHO Grade II), anaplastic ependymoma (Grade III), myxopapillary ependymoma (Grade I), and subependymoma (Grade I) as well as the ependymal variants (cellular, papillary, epithelial, clear cell, and mixed). Whereas ependymomas occur in both children and adults, subependymomas and myxopapillary ependymomas are more common in adults.…”
Section: Neurosurg Focus / Volume 19 / November 2005mentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth ventricle is the most common location for ependymomas. Cellular and anaplastic ependymoma are WHO grades II and III, respectively (12). Despite in vivo MRS spectra from both cellular and anaplastic ependymomas exhibiting considerable heterogeneity, their metabolic common profile include lower relative levels of N-acetyl-aspartate (NAA) in comparison to other tumours (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%